Answers:
- a)

- b)

Each answer has 7 as the base and a fraction as an exponent.
==========================================================
Step-by-step explanation:
One useful rule here is that
. The fraction m/n is the exponent for the base x. Note how the index of the root (n) becomes the denominator of the fraction m/n. So for example if we had n = 3, then we'd be dealing with a cube root.
For part a), we have x = 7, m = 1 and n = 5 to get
![\sqrt[n]{x^m}=x^(m/n)\\\\\sqrt[5]{7^1}=7^(1/5)\\\\\sqrt[5]{7}=7^(1/5)\\\\](https://img.qammunity.org/2022/formulas/mathematics/high-school/6zebftv39tible4dp158q6ati62m8lecf6.png)
-----------------
Part b) is the same idea
We would find that
![\sqrt[n]{x^m}=x^(m/n)\\\\\sqrt[7]{7^1}=7^(1/7)\\\\\sqrt[7]{7}=7^(1/7)\\\\](https://img.qammunity.org/2022/formulas/mathematics/high-school/shgtbtjgvj010hmdy6i1s44frzzvqcwp35.png)
Then apply the reciprocal to both sides. This is the same as raising both sides to the exponent -1
![\sqrt[7]{7}=7^(1/7)\\\\\left(\sqrt[7]{7}\right)^(-1)=\left(7^(1/7)\right)^(-1)\\\\\frac{1}{\sqrt[7]{7}}=7^(1/7*(-1))\\\\\frac{1}{\sqrt[7]{7}}=7^(-1/7)\\\\](https://img.qammunity.org/2022/formulas/mathematics/high-school/wmp30cwnbxsx64cx5zoqmufd6dy6wcevx1.png)
You could also use the rule that x^(-y) = 1/(x^y) when dealing with negative exponents.
In the second to last step shown above, I used the rule (x^y)^z = x^(y*z) on the right hand side.